An evaluation of the performance of the goat dispersal project in pilot barangays of Negros Occidental - Elican, Jabez Redil (Iloilo City University of the Philippines in the Visayas, 2005)
The Goat Dispersal Project in the pilot barangays of Negros Occidental, specifically in Barangays Pinowayan and Bagong silang of Don Salvador Benedicto, is one of the activities in support to the thrust of the reforestation activity of the Provincial Environment Management Office. This study entitled "An Evaluation of the Performance of the Goat Dispersal Project in Pilot Barangays of Negros Occidental" was conducted based on the following objectivehe target beneficiaries ; and to identify problems encountered in the implementation of the program. This study aims to provide baseline information informulating policy recommendation for a more effective and efficient implementation of the project. Descriptive analysis was applied on data obtained from a survey questionnaire.Frequencies, percentages and ranking were employed in the analysis of data. Scaling techniques were utilized in assessing the level of satisfaction on the project using thecategories : Very satisfied (VS), Satisfied (S) and Not Satisfied (NS) while for the overall performance, the ratings used were Very Good, Good and Not Good. The forty four (44) goatbeneficiaries who are also Integrated Social Forest (ISF) members were the respondents of the study. Majority of them are married and between 41-60 years old. The respondents arecomposed of 50 percent male and 50 percent female. Most of them have 6-10 family members and with 77 percent of them attended elementary level. Their socio-economic profile indicates that almost 62 percent have semi-permanent houses, most of them usekerosene lamp as source of light and spring water coursed through pipes was the source of water for the majority. Transistor radios and wall clocks are the household assets available to most of them. Results regarding the attitude of the respondents show that most believe the project gives them benefits and that they want to raise additional goats. The overall performance of the project was prceived as " good" by majority of the respondents (77%). Most of them are "satisfied" claiming that the project has resulted to improved living conditions, improved status in life, increased production and income. broadened knowledge in goat raisning, developed a sense of responsibility among beneficiaries thus goat raising has become a part of their lives. The lack of capital and thievery were the constraints perceived by the majority of the respondents.
[Research Paper] (Management 299 -Research methods and techniques) -- Iloilo City :U. P. in the Visayas, November 2005.s : to describe the socio-economic condition ofthe two pilot barangays ; to evaluate the effectiveness of the goat dispersal project in augmenting income and improving the socio-economic condition of t